Analisa Implementasi Sistem Absensi Sidik Jari Guru Min Peukan Baro - Iqlima Iqlima; Taufiq Taufiq; Munar Munar (Jurnal Tika, 2023)
The development of science in all fields in the current era of globalization is so rapid, especially in the field of Information Technology (IT) which is increasingly advancing along with user needs. Min Peukan Bada School is one of the many government agencies or schools that utilize information technology in their operational activities. One of the information technologies applied at Min Peukan Bada is attendance software using a fingerprint. The purpose of this study is to analyze the existing fingerprint system at MIN Peukan Bada which is already running. The method used in analyzing the system is how to find the standard error value and find the percentage of success from the fingerprint system that is already running. The results of the study are a desktop-based application that can be used to manage employee data and conduct training and testing of employee fingerprint images so that the final result is the percentage of success in employee fingerprint recognition at the MIN Peukan Baro school